Mechanical properties of clay brick masonry bound with hydraulic limes and hydrated calcium lime. - COSTIGAN, ADRIAN; PAVIA, SARA (Technische Universitat Dresden, 2010)
Due to their physical and chemical properties, mortars made with lime are considered to be more compatible with historic fabrics than those made with artificial cements. This paper explores the mechanical properties of clay brick masonry bound with hydraulic limes of different strengths, and hydrated calcium lime (CL90-s) with no hydraulic properties. Masonry wallettes built with a CL90-s mortar and two natural limes of hydraulic strengths 3.5 and 5 MPa (NHL 3.5 and NHL 5) respectively were tested for compressive and flexural strength. The strength of the bond between the mortar and the brick was also measured. The paper concludes that CL mortar masonry displays a plastic behaviour in compression while the mechanical behaviour of the HL mortar masonry is of a brittle nature, with wallettes splitting along the centre, cracks above and below the vertical joints and spalling of brick and mortar. It also concludes that neither the rate of late strength gain of masonry, nor its ultimate compressive strength or its bond strength are determined by the mortar nature, thus a mortar of low hydraulic strength can provide stronger masonry than an emminetly hydraulic mortar. The paper agrees with previous authors on that the masonry?s compressive strength is more sensitive to the brick-mortar bond strength than to the compressive strength of the mortar. Finally, the paper demonstrates that the NHL-mortar compressive strength increases at a higher rate, and reaches higher final values than that of the NHLmasonry whereas, in contrast, the CL90-s mortar is weaker in compression than the CL90-s mortar masonry.
PUBLISHED
Keywords: Construction engineering; CL mortar; hydrated lime; NHL mortar